A new Salmonella tester strain (TA102) with A X T base pairs at the site of mutation detects oxidative mutagens. - Levin, D E (1982)
A new tester strain, TA102, is described as an addition to the set of strains for the Salmonella/microsome mutagenicity test. This strain contains A X T base pairs at the site of the mutation (determined by DNA sequence analysis) in contrast to the other Salmonella tester strains that detect mutagens damaging G X C base pairs. This strain differs from previous tester strains in that the mutation has been introduced into a multicopy plasmid, so that approximately equal to 30 copies of the mutant gene are available for back mutation. The new strain detects a variety of oxidative mutagens, including x-rays, bleomycin, hydrogen peroxide and other hydroperoxides, streptonigrin and other quinones, and phenylhydrazine; a variety of aldehydes, including formaldehyde, glyoxal, kethoxal, glutaraldehyde, and malondialdehyde; a number of psoralens (in the presence of near-UV light), mitomycin C, neocarzinostatin, and UV light. Some of these mutagens have been previously shown to damage thymine in DNA. Several auxiliary tester strains also are described, including TA96, a frameshift tester strain with a hot spot for mutation at a run of five A X T base pairs with a specificity similar to that of TA102. The importance of oxidative mutagens is discussed.